2010
DOI: 10.1111/j.1365-2958.2010.07142.x
|View full text |Cite
|
Sign up to set email alerts
|

New mechanistic insights into pre-protein transport across the second outermost plastid membrane of diatoms

Abstract: SummaryChromalveolates like the diatom Phaeodactylum tricornutum arose through the uptake of a red alga by a phagotrophic protist, a process termed secondary endosymbiosis. In consequence, the plastids are surrounded by two additional membranes compared with primary plastids. This plastid morphology poses additional barriers for plastid-destined proteins, which are mostly nucleus-encoded. Recent investigations have focused on the postulated translocon of the second outermost membrane (periplastidal membrane, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 30 publications
1
46
1
Order By: Relevance
“…Besides such synthetic constructs, we screened all known endogenous PPC proteins (9,10,13,16,(29)(30)(31) for potential N-glycosylation sites using the program NetNGlyc 1.0. Interestingly, 23% of the 52 proteins possess potential N-glycosylation sites with high confidence predictions (++) within the mature, soluble protein (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides such synthetic constructs, we screened all known endogenous PPC proteins (9,10,13,16,(29)(30)(31) for potential N-glycosylation sites using the program NetNGlyc 1.0. Interestingly, 23% of the 52 proteins possess potential N-glycosylation sites with high confidence predictions (++) within the mature, soluble protein (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was proposed that transport across the second plastid membrane of diatoms is mediated by an ER-associated degradation (ERAD)-derived translocation machinery, which was termed symbiontspecific ERAD-like machinery (SELMA) (12,13). Phylogenetic data together with molecular analyses suggest that during evolution, core components of the red algal ERAD-transport system were relocalized from the symbiont's ER to the second plastid membrane to mediate preprotein translocation (12)(13)(14)(15)(16). After transport across the second membrane, two main protein populations have to be discriminated: proteins that remain within the space between membrane two and threethe periplastidal compartment (PPC), which corresponds to the cytosol of the red algal endosymbiont-and proteins that are destined to the plastid stroma and have to be transported across two further membranes (Fig.…”
mentioning
confidence: 99%
“…Core components of the ERAD machinery, such as Der1 proteins, Cdc48 with its cofactor Ufd1, and a complete set of proteins needed for ubiquitination (E1, E2, E3 enzymes and ubiquitin itself), have been shown to be present in two versions in cryptophytes, heterokontophytes, haptophytes and apicomplexa. One set of these ERAD factors is specific for the host cell, whereas the second version originates from the red algal endosymbiont [21,[23][24][25][26]85]. As the symbiont's ER is not retained within the periplastidal compartment (PPC), which is derived from the former cytosol between membranes two and three, it was concluded that those symbiont-specific factors might play an ERAD-independent role, such as that of a protein translocation system across the second outermost plastid membrane [24].…”
Section: Pr Ospects and Overviews K Bolte Et Almentioning
confidence: 99%
“…These components are indeed involved in the transport of proteins into the plastid as indicated by a conditional knock-down mutant of the Toxoplasma gondii sDer1 protein which showed impairment in plastid protein import (2). The translocation process is predicted to be dependent on ubiquitylation, further supported by the presence of a set of ubiquitylation enzymes (39,67). Additional factors proposed to be involved in SELMA are a symbiont-specific Cdc48 AAA-ATPase with its cofactor Ufd1 and adaptor proteins (55,67).…”
mentioning
confidence: 98%
“…Additional factors proposed to be involved in SELMA are a symbiont-specific Cdc48 AAA-ATPase with its cofactor Ufd1 and adaptor proteins (55,67). After translocation, the precursor proteins are likely to undergo deubiquitylation and are either passed on to the translocon in the third outermost membrane or folded in the PPC (13,39,55). Although a residual set of 20S proteasomal components was identified in the PPC of diatoms, there is currently no link between SELMA and proteasomal degradation (55).…”
mentioning
confidence: 99%